Preliminary analysis of landslides induced by the 3 April 2024 Mw 7.4 Hualien, Taiwan earthquake: Preliminary analysis of landslides induced by the 3 April 2024 Mw 7.4 Hualien, Taiwan earthquake - Chen, Yi; Song, Chuang; Li, Zhenhong; Chen, Bo; Yu, Chen; Hu, Jyr-Ching; Cai, Xingmin; Zhu, Shuang; Wang, Qianwen; Ma, Yixin; Gu, Changjun; Li, Suju; et al. (Landslides, 2025)
On 3 April 2024, a Mw 7.4 earthquake occurred in Hualien County, Taiwan, the largest earthquake in 25 years for this region, causing 18 deaths and inducing a large number of geological hazards. Based on the impact of this event, we conducted a preliminary investigation of the geological hazards induced by the Hualien earthquake using medium-to-high resolution remote sensing images. The results of remote sensing image interpretation indicated that the Hualien earthquake induced 1,243 landslides, with a total area of about 21.5 km 2 , the smallest area of about 393 m 2 , and the largest area of about 0.34 km 2 . Most were small landslides, distributed on both sides of the river valleys or in the coastal zone. By integrating topographic, geomorphic, seismic, and geological factors, the spatial distribution pattern of earthquake-induced landslides was analyzed in detail: (1) Landslides were prone to occur at elevations of 800–2,000 m, on the east- and south-east-facing slopes at 40°-45° and with low vegetation cover; (2) high peak ground acceleration (PGA) (0.42–0.44 g) and peak ground velocity (PGV)(> 50 cm/s) tended to trigger more landslides; (3) Landslides were mainly concentrated in schist and gneiss. In addition, by analyzing global and local features using the Random Forest (RF) and SHapley Additive exPlanations (SHAP) models, we found that strong shaking was the main controlling factor for earthquake-induced landslides in Hualien, followed by the Normalized Difference Vegetation Index (NDVI) factor, suggesting that the distribution of earthquake-induced landslides was strongly correlated with the vegetation cover. Therefore, for earthquake-prone areas such as Taiwan, a reasonable vegetation cover management policy in mountainous areas is of great significance in reducing the occurrence of earthquake-induced geological disasters.